Prototype of Personal Knowledge Management on Higher Education - Ilyas Nuryasin (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
This study proposed a prototype of personal knowledge management system on higher education. Personal knowledge management system is a method that used by person to manage his own knowledge. The knowledge will be classified and stored  in the databases system and retrieved when needed. This study is focused for the students who take courses during undergraduate program period. All academics activities will be recorded in the system and published as portfolio on the end of study as a complementary document along certificate and transcript. This prototype offers the students to manage their knowledge from their projects, prototypes, patents, researches, seminars and work experiences.